PENGARUH POLITICAL CONNECTION, COMPENSATION EXECUTIVE, DAN SALES GROWTH TERHADAP TAX MANAGEMENT PADA PERUSAHAAN YANG TERDAFTAR DI INDONESIA STOCK EXCHANGE - Yohanes Mardinata Rusli (JURNAL LENTERA AKUNTANSI, 2020)
The main purpose of this research is to find out how much tax management is carried out by companies in carrying out tax planning. This study aims to determine and analyze the influence of political connections, compensation executives, and sales growth on tax management. The population in this study is publicly traded companies that are not in the financial sector. The methodology in this study uses a purposive sampling method through predetermined criteria, and obtained 18 companies that are sampled in this study. The data used are secondary data in the form of company annual reports for the 2015-2018 reporting period. Data is collected using quantitative techniques from secondary sources from the company's annual report to be studied. In this study, researchers used panel data analysis. Based on the test results using multiple linear regression for panel research data, it can be concluded that: (1) political connections do not have a significant effect on tax management; (2) compensation executive has no significant effect on tax management; (3) sales growth has a significant effect on tax management. Keywords:political connection, compensation executive, sales growth, tax management.